Desempenho financeiro das empresas sustentáveis que participam do índice do carbono eficiente - Carvalho, Patrícia Lacerda de (2015)
Based on Stakeholder Theory, this dissertation sought verifying whether there is a relation of superiority regarding financial performance of companies that are member of Carbon Efficient Index (ICO2) against the ones that are only member of the marketing indices from BM&FBovespa: IBOV, IBrX-50, and IBrX-100. Initially, we have compared the members of ICO2 with the exclusive members from market indices, characterizing their portfolios and analyzing their market sectors. At a second moment, an analysis of liquidity and companies’ market stock return was conducted. Thereafter, a performance evaluation about these companies was carried out considering financial indicators from Sharpe, Treynor, and Jensen. The data analysis was limited to the period from September 2010 to December 2014 and the sample data comprised four indices from BM&Bovespa – ICO2, IBOV, IBrX-50, and IBrX-100. We have used Economatica system to extract market stock data from the companies selected. In this study we have decided to exclude shares that participated, simultaneously, in the stock market indices and ICO2 index. This dismemberment elucidated the large quantity of companies that were both member of ICO2 and stock market indices at the same time. We inferred that there is concern with sustainability investment between the companies member of the market indices which provide a satisfactory market perspective. We have observed distinct compositions on the indices analysed considering companies' portfolio characterization regarding the actuation sector. It's relevant to highlight that Finance and Insurance sector was the most representative sector at ICO2 portfolio. We analysed the liquidity using Board Liquidity and Average Volume. After the analysis, it has been noted that IBrX-50 companies got the best results followed by the sustainable companies. The companies' market stock return was evaluated by nonparametric tests such as Kruskal-Wallis, Wilcoxon, and Mann-Whitney. Despite the fact that ICO2 have gotten the best result, overcoming the selected indices, there was no statistically significant connection among the historical series about the return of the indices. We have applied Engle-Granger (1987) cointegration test in order to infer any relevance on the long-term. The results take to an existence of a linear combination between the series of returns indices based on average returns. We had also inspected the performance of the indices considering Sharpe, Treynor, and Jensen indicators. This result imply that the ICO2 had the best performance according to Sharpe and Jensen indices still it was not very significative. Regarding the Treynor index, the ICO2 overcome the results of the marketing indices in the period analyzed. Thus, the relationship of superiority between the financial performance of sustainable business to their companies that are not classified as could not be confirmed.